Voltage‐Induced ON Switching of Magnetism in Ordered Arrays of Non‐Ferrimagnetic Nanoporous Iron Oxide Microdisks. Issue 1 (20th November 2020) - Cialone, Matteo; Nicolenco, Aliona; Robbennolt, Shauna; Menéndez, Enric; Rius, Gemma; Sort, Jordi
Abstract: Tailoring the magnetic properties of ordered arrays of patterned structures usually requires stringent control of their size, pitch, microstructure, and composition. Here, a fundamentally different approach to manipulate the magnetic behavior of lithographed microdisks, based on the application of electrical voltage, is demonstrated. First, highly porous iron oxide films with virtually no magnetic response (OFF state) are grown by sol–gel chemistry. Subsequently, arrays of microdisks (8 µm in diameter) are obtained combining lithography with wet chemical etching processes. Electrolyte‐gating (with an anhydrous electrolyte) is then employed to induce a tunable (i.e., "on‐demand") ferromagnetic response in these disks (OFF–ON switching of magnetism) at room temperature. The changes in magnetic properties are attributed to magnetoelectrically‐driven oxygen ion migration, which is enhanced due to nanoporosity. This causes partial reduction of the oxide phases to metallic Fe. The effect can be considerably reversed by applying voltage of opposite polarity. These results are appealing for diverse technological applications that require the use of patterned structures with easily tunable magnetic properties, such as magnetic micro‐electro‐mechanical systems, microfluidic, and lab‐on‐a‐chip platforms for biomedical therapies and, ultimately, energy‐efficient magnetic memories or neuromorphic computing. Abstract : Voltage‐driven switching of magnetism is accomplished in arrays of nanoporous FeO x microdisks by applying electrical voltage. After pattern fabrication, the magnetic properties can be controlled, at will, by varying the strength of voltage. The effect is primarily governed by voltage‐induced oxygen ion migration, which triggers phase transformations. The induced magnetism can be substantially removed by reversing the voltage polarity.